(untitled) (Avocetta, 2017)
The knowledge about the presence and the distribution of the Golden Eagle Aquila chrysaetos in the Abruzzo Region up to the end of ‘900 is probably partial and not exhaustive. In the paper “Birds of Abruzzo and Molise” by the ornithologist Nicola De Leone, with observations from 1908 up to 1932, this species is frequently reported as present in several municipalities (De Leone 1933). In more recent papers the number of known pairs is between 8 and 14. Presence and distribution data have been further analyzed in “Central Apennines” (Chiavetta 1978, Zocchi 1992, Allavena et al. 1997, Spinetti 1997, Borlenghi & Corsetti 2002). In 2003, the Abruzzo ornithological station promoted a full survey over all of its territory, revealing the presence of 16 territorial pairs, confirmed through nests in the administrative boundaries of the region (Magrini et al. 2007). Other breeding pairs were present in Abruzzo but they were found nesting just outside the administrative borders (Artese pers. obs.). Since 2003, monitoring continued uninterruptedly for the entire population, although some pairs were not studied. The Abruzzo region covers 10795 km2, 7029 of which are classified as mountain. Excluding the urbanized areas of Aquilana, Peligna and Fucino planes, the remaining territory foothills and mountain is suitable for this species.